Implementasi Metode Real Experiments dan Virtual Experiments Pada Pembelajaran Fisika di SMAN 1 Kediri - Hikmawati Hikmawati; Kusmiyati Kusmiyati; Sutrio Sutrio; Edi Kurniawan; Halimatus Sakdiyah (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This study aims to analyze the results of the implementation of learning methods namely real experiments and virtual experiments on learning physics in SMAN 1 Kediri. In the real experiment method three-dimensional media is used, whereas in the virtual experiment method computer simulation in the form of Physics Education Technology (PhET) is used. Learning tools used consist of syllabus, learning implementation plans, subject matter books, learning media, student worksheets, and learning outcome tests. Test subjects are limited to learning devices using learning methods namely real experiments and virtual experiments are students of Class XI Science 1 in SMA 1 Kediri Academic Year 2017/2018. The learning model applied is inquiry with 6 stages, namely identification and formulation of problems, formulation of hypotheses, data collection, data interpretation, development of conclusions, repetition. Learning activities are carried out in 4 meetings. Assessment of the implementation of learning using a scale of 4 with criteria that is a score of 12 to 16 including very good criteria, a score of 8 to 11 including good criteria, scores 4 to 7 including poor criteria, and scores less than 4 including bad criteria. Based on the data analysis obtained the average value of learning implementation for 4 meetings is equal to 14. Thus it can be concluded that the implementation of learning methods namely real experiments and virtual experiments on learning Physics at SMAN 1 Kediri are very good criteria.